A Critical Review of the Effectiveness of Online Marketing Strategies in Ecommerce Platforms (International Journal of Food and Nutritional Sciences, 2022)
Although offline advertising techniques are frequently used, they are also up against severecompetition against online advertising, which offers countless options and vast opportunities.